Seasonal vertical distribution of fish larvae in the southern Gulf of Mexico - Espinosa-Fuentes, María de la Luz; Flores-Coto, César; Zavala-García, Faustino; Sanvicente-Añorve, Laura; Funes-Rodríguez, René (HIDROBIOLÓGICA, 2017)
Changes in the composition and abundance of fish larvae in the water column were analyzed throughout an annual cycle (1994-1995) in the southern Gulf of Mexico, in order to establish the difference between the habitat of the larvae and the effect of oceanographic events on larval vertical distribution. The study area comprised the continental shelf off Tabasco and Campeche in the southern Gulf of Mexico. Samples were collected at five water column levels: 0-6, 6-12, 12-18, 45-55 and 95-105 m. A total of 118 taxa were identified, 52 were dominant species, 33 were larvae of neritic parents and 19 were larvae of mesopelagic parents. The results indicate that the water column presented two layers above the 105 m depth: a surface layer (0-18 m) and a deep layer (45-105 m). The greatest density of larval species that inhabit neritic areas as adults was recorded in the surface layer (0-18 m), while larvae of which the parents inhabit mesopelagic areas were found in the deep layer (45-105 m). The mixing of the water column was the most important physical factor regarding the variation in the vertical distribution of the larvae of both groups, particularly in winter. However, the biology of each species and the habit to occupy a particular depth was the most important factor that determined their distribution in the water column.